PELATIHAN KOMPUTER PROGRAM MICROSOFT EXCEL 2013 PADA SMAN 12 BANJARMASIN - Auliya Rahman; Fitrah Yuridka; Mayang Sari (Universitas Islam kalimantan MAB, 2015)
One concept in Educational Technology is the utilization and empowerment of learning resources in the learning process to increase the activity of learners. Computer as a source of learning can provide a very large contribution in improving the quality of education. Microsoft Excel 2013, is a means to convey information that is used by many. By using Microsoft Excel 2013 delivery of any information would be obtained with ease. The purpose of community service is to implement a technology-based education and information for teachers so as to improve human resources in particular lecturer as well as a teacher at SMAN 12 Banjarmasin. This training is expected to make it easy for teachers in teaching and learning activities, and can make learning and teaching more attractive; provide skills to teachers in the use of office applications in everyday life in order to facilitate the teaching and learning activities; and creating technology-literate faculty that later can print human resources better. To support the expertise of educators / teachers at SMAN 12 Banjarmasin in the field of information technology used approaches through training with the use of modules. In this training taught how to run an application Microsofs Excel 2013 as govern the writing of the formulas that are very useful to recapitulate the value of the student or the administration, which will be presented in an interesting so that participants will be easy to understand and can be applied to teaching and learning activities of daily.